High‐protein rice‐soya breakfast cereal - Bakar, Jamilah; Hin, Yap Sui (Wiley Blackwell, 1985)
The effect of three particle sizes and three different percentages of full‐fat soya flour was studied for development of a high‐protein rice‐soya based reakfast cereal. Proximate analysis, essential amino acid profile, percentage water‐holding capacity (WHC), crispiness and sensory evaluations were carried out for formulated flakes. The substitutions of 10, 20 and 30% full‐fat soya flour for rice flour achieved good essential amino acid profiles but only the formuations with 20 and 30% soya flour qualified as high‐protein flakes as reflected by their protein‐calorie ratios (PCR) of approximately 15 and 19, respectively. The WHC of flakes was not affected by the percentage of soya flour used for the coarse (710 μm) and the medium (500 μm) particle size soya flour. The WHC of flakes formulated from fine (355 μm) particle size soya flour increased with the percentage of soya flour used. Crispness of flakes generally decreased with increasing percentage of soya flour at the 20 and 30% level. An inversely proportional relationship between crispiness and the particle size of soya flour was observed at the 30% level of substitution. Panelists did not show any trend in the overall preference of flakes developed.